The strategic direction of the Colleges of Physical Education and Sports Sciences at the University of Baghdad (Damu Journal of Sport Sciences, 2025)
The current research aimed to identify the extent of strategic orientation in the College of Physical Education and Sports Sciences at the University of Baghdad and the correlation between research variables. The study was conducted on a sample of (220) college instructors, representing (80%) of the original population. A scale (strategic orientation) was constructed by identifying (4) main areas distributed among them (28) paragraphs. The questionnaire was selected as a tool to set the scale requirements in the research format and distributed to an application sample of (90) instructors, representing (40.9%) of the sample as a whole. The data were then processed through the (SPSS) system according to the statistical requirements of the research to achieve the research objectives. The results revealed the presence of strategic orientation in a practical way through the sample's responses according to the research paragraphs. The most important The conclusions are that strategic orientation is one of the driving forces for competition and excellence with other specialized colleges and the sustainability of its success. The college's orientation is to understand the requirements and desires of the labor market, which aligns with the academic subjects and develops strategic objectives. It recommended investing in positive relationships with stakeholders and how to benefit from their ideas and aspirations and employ them in consolidating the college's future outcomes. It also emphasized the need for knowledge communication and scientific partnerships with similar colleges locally and internationally to enhance the college's scientific, technical, and administrative efficiency and capacity within the strategic orientation for future goals.